AVALIAÇÃO DAS COMPLICAÇÕES PÓS-OPERATÓRIAS IMEDIATAS DOS PACIENTES SUBMETIDOS À CIRURGIA DE TUMOR DE HIPÓFISE - Santos, Kenya Mara Veras (2012)
The pituitary adenomas are the most common cause of a sellar mass of the third decade onwards, accounting for more than 10% of intracranial tumors. Recent studies indicate a prevalence of up to 77.6 per 100,000 inhabitants. Postoperative complications of hypophyseal surgery include: lesion of the carotid artery, cerebrospinal fluid leak, nasal septum perforation, Diabetes Insipidus, Syndrome of Inappropriate Antidiuretic Hormone Secretion, adrenal insufficiency, epistaxis, hyponatremia, sinusitis, visual loss, transient paralysis of the cranial nerve, sphenoidal abscess, meningitis, hemorrhage in the tumor bed and hypothalamic injury. Being the last three the ones of the highest mortality. This study evaluated 28 patients undergoing surgery of Pituitary tumor by transsphenoidal way and 2 by transcranial and watched the most common complications such as: cerebrospinal fluid leak (30 %), Diabetes Insipidus (26.6 %) and adrenal insufficiency (13.3 %) were found more frequently , followed by bleeding in the tumor bed (6.7%), pneumonia (6.7%) and sinusitis (3.3%). The prevalence of mortality was 6.7%. Endocrine complications can lead to death if not treated timely. A thorough clinical and laboratory evaluation by a multidisciplinary team is necessary for good performance in the management of postoperative complications of patients undergoing resection of pituitary tumor, since anticipate complications and minimize its risks.